Joseph's Platz, Vienna - Redaway, James (engraver):::Creator::::::::::::; Batty, Robert, 1789-1848 (artist):::Contributor:::::::::::: (United Kingdom; London; Rodwell & Martin)
Color engraving of Joseph's Platz, Vienna, Austria